2017
DOI: 10.1123/jsr.2016-0003
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Effects of Proprioceptive Neuromuscular Facilitation Stretching Programs Compared With Passive Stretching Programs for Hamstring Flexibility: A Critically Appraised Topic

Abstract: Clinical Scenario: Increasing hamstring flexibility through clinical stretching interventions may be an effective means to prevent hamstring injuries. However the most effective method to increase hamstring flexibility has yet to be determined. Clinical Question: For a healthy individual, are proprioceptive neuromuscular facilitation (PNF) stretching programs more effective in immediately improving hamstring flexibility when compared with static stretching programs? Summary of Key Findings: A thorough literatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 8 publications
2
9
1
3
Order By: Relevance
“…In our study, we have found that the stiffness of the hamstring decreased significantly after PNF stretching, which is in agreement with the results reported by Konrad et al (2015) , and supports previous findings ( Hill et al, 2017 ; Lempke et al, 2018 ). While the detailed mechanism underlying the reduction in muscle stiffness after PNFS is unknown, the acute effects of PNFS on the properties of intramuscular connective tissue such as endomysium, perimysium, and apparent may also contribute to the reduction in muscle stiffness after PNF stretching.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, we have found that the stiffness of the hamstring decreased significantly after PNF stretching, which is in agreement with the results reported by Konrad et al (2015) , and supports previous findings ( Hill et al, 2017 ; Lempke et al, 2018 ). While the detailed mechanism underlying the reduction in muscle stiffness after PNFS is unknown, the acute effects of PNFS on the properties of intramuscular connective tissue such as endomysium, perimysium, and apparent may also contribute to the reduction in muscle stiffness after PNF stretching.…”
Section: Discussionsupporting
confidence: 93%
“…It has been also demonstrated that a reduction in shoulder pain through training protocols, including stretching exercises in the training sessions and causing an improvement in shoulder ROM, was directly related with stability and pain [32]. Moreover, other studies with older women have shown an association between greater ROM, an increase in daily life activities, and quality of life [34,35]. The result obtained by our study showed that the MT group obtained a greater effect on quality of movement, measured by the FMS effect size, than the MFT group, even though the latter presented a functional improvement, which could contribute to better performance in daily life activities (DLAs).…”
Section: Discussionmentioning
confidence: 99%
“…Research shows static stretching as the most effective method for increasing flexibility [32]. A possible explanation for a greater increase in flexibility is that stretching reduces the viscosity of the tendon structure [33], but increases elasticity, which is mainly caused by a reduction in passive stiffness of the muscle-tendon unit and tonic reflex activity [34].…”
Section: Resultsmentioning
confidence: 99%